2005
DOI: 10.1126/science.1107403
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian SAD Kinases Are Required for Neuronal Polarization

Abstract: Electrical activity in neurons is generally initiated in dendritic processes then propagated along axons to synapses, where it is passed to other neurons. Major structural features of neurons-their dendrites and axons-are thus related to their fundamental functions: the receipt and transmission of information. The acquisition of these distinct properties by dendrites and axons, called polarization, is a critical step in neuronal differentiation. We show here that SAD-A and SAD-B, mammalian orthologs of a kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
387
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(417 citation statements)
references
References 23 publications
19
387
1
Order By: Relevance
“…Interestingly, we found that the levels of SAD kinases and phosphorylated LKB1 (pLKB1) at S431, an active form of LKB1, were markedly decreased in the hippocampus or cortex of Itgb1 f/f ; Emx1-Cre mice ( Figure 4A). In line with this observation, we found that the level of phosphorylated Tau (pTau) at S262, the consensus phosphorylation site by SAD kinases [13], was decreased in these Itgb1-deletion mice ( Figure 4A). Thus, Itgb1 plays an important role in maintaining the levels or activity of , and plated onto coronal cortical slices from P0 rats.…”
Section: Itgb1 Regulation Of Neuronal Polarity Proteinssupporting
confidence: 69%
See 3 more Smart Citations
“…Interestingly, we found that the levels of SAD kinases and phosphorylated LKB1 (pLKB1) at S431, an active form of LKB1, were markedly decreased in the hippocampus or cortex of Itgb1 f/f ; Emx1-Cre mice ( Figure 4A). In line with this observation, we found that the level of phosphorylated Tau (pTau) at S262, the consensus phosphorylation site by SAD kinases [13], was decreased in these Itgb1-deletion mice ( Figure 4A). Thus, Itgb1 plays an important role in maintaining the levels or activity of , and plated onto coronal cortical slices from P0 rats.…”
Section: Itgb1 Regulation Of Neuronal Polarity Proteinssupporting
confidence: 69%
“…The upregulation of ILK may reflect homeostatic intracellular responses to the loss of Itgb1. Next, we determined states of LKB1 and SAD kinases, which are known to be essential for axon formation both in vitro and in vivo [12][13][14]. Interestingly, we found that the levels of SAD kinases and phosphorylated LKB1 (pLKB1) at S431, an active form of LKB1, were markedly decreased in the hippocampus or cortex of Itgb1 f/f ; Emx1-Cre mice ( Figure 4A).…”
Section: Itgb1 Regulation Of Neuronal Polarity Proteinsmentioning
confidence: 94%
See 2 more Smart Citations
“…76 The KIGS or KCGS motifs in the repeat domain (S262, S293, S324, S356) can be phosphorylated by MARK, PKA, PKB, SADK, CaMKII, and p70S6K. [77][78][79][80] PKA additionally phosphorylates other sites including S214, a phospho-epitope that is especially upregulated during mitosis. 81 In AD brain, tau is hyperphosphorylated at nearly all phosphorylation sites, with approximately nine phosphates per molecule, in contrast to the two to three phosphorylated residues observed in healthy control brains.…”
Section: Antiphosphorylation Strategiesmentioning
confidence: 99%